Smoking cessation – better together: A retrospective cohort study - Limor Adler; Shafeek Abu Arar; Ilan Yehoshua; Bar Cohen; Sharon Hermoni Alon; Arnon Shahar; Galia Zacay; Miri Mizrahi Reuveni (Tobacco Induced Diseases, 2023)
Introduction Smoking is the leading preventable cause of death and illness globally. There is conflicting evidence regarding the association between quitting rates and partners’ smoking status. It is thought that spouses influence one another’s health habits, including smoking. This study aims to evaluate this association in patients who made a smoking cessation attempt with pharmacotherapy.